Influence of humidity on the emergence of Ceratitis capitata in two types of soil - Azevedo, Eliane M. Milward de; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out in arder to study the effect of moisture in two soils on the emergence of Ceratitis capitata (Wied, 1824) (Diptera, Tephritidae), usin soil moisture retention curves. Six soil moisture tensions were used for each soil: ; - 10-³ ; - 5x10-³; - 10-²; 3x10-²; - 10-¹ and - 1.5 MPa which correspond to 32.8; 21.5; 15.7; 9.5; 7.6 and 5.5 of gravimetric moisture percent for the "Podzolizado Vermelho-Amerelo variação Lins" soil (sandy soil) and 59.9; 46.5; 40.5; 30.3; 26.0 and 21.1 of gravimetric moisture percent for the "Latossolo Vermelho-Escuro distrófico, textura argila" soil (clay soil). C. capitata has had a different behavior in both soils. In the sandy soil a shorter pupal period was obtained in the wet conditions. On the other hand in the clay soil there were no differences in all treatments for the duration of the pupal period. The viability of the pupal was greatly affected in the clay soil, where there were obtained higher values in the clay conditions, in the sandy soil the higher values were obtained in the intermediate tensions of moisture. There were no differences between males and females for both soils. The emergence period was concentrated in the wet conditions.